Penyadaran Berzakat, Berinfaq, dan Bersodaqoh untuk Pemberdayaan Umat - Moh. Turkan Badri; M. Yunus; Musyaffa Rafiqie; Mohamad Aso Samsudin; Shokhibul Migfar; Djuwairiyah Djuwairiyah (LP2M Universitas Ibrahimy, 2024)
Zakat, infaq, and shodaqah were once sources of state income to empower the people. This fact occurred in the early golden era of Islam, so zakat or obligatory zakat institutions at that time had difficulty distributing zakat because zakat was already evenly distributed and met the needs of its recipients. This fact is different from the facts today, where zakat, infaq, and shodaqah have not been able to empower the people. There is an idea to revitalize the function of zakat through raising awareness in the community. This study is a literature study by collecting literature supporting this idea's achievement. The results of this study show that empowerment of the people can be pursued again by providing awareness to the people to pay zakat and managers to carry it out according to applicable regulations, whether according to fiqh or legislation.